A model for the effective utilisation of mobile payment systems in Zimbabwe’s retail sector - Sibadhlile, Stanford (Midlands State University, 2017)
This model was developed with close reference to the model used by Japan in their implementation of Mobile Suica – a mobile wallet system which has served their transport woes since 2001.The findings from this research showed that the previously proposed model for the adoption and acceptance of mobile technology, the TAM and the UTAUT can fully apply to the Zimbabwean economy with the additional of three more constructs which are political influence, economic influence and interoperability of MNOs. In this research, the researcher recommended that in order to increase the utilisation of mobile money in the retail sector, more retailers must register as merchants so that consumers can use the m-payment facility. The MNOs should also reduce their tariffs so that it becomes cheaper and convenient for the consumer to make payments through a mobile money system. Further studies should focus on the utilisation of mobile money in other facets of the retail sector to include fast food outlets, hardware shops and fashion shops.